2012
DOI: 10.1021/es3025935
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of Technetium from Reduced Sediments under Seawater Inundation and Intrusion Scenarios

Abstract: Predicted sea level rise would increase the vulnerability of low lying coastal legacy nuclear sites to inundation and intrusion with oxygenated seawater. This could have a significant impact on the mobility of redox-sensitive radionuclides such as Tc. Here, batch and column experiments were used to simulate and investigate the effect of these processes on the mobilization of Tc from sediments under a range of geochemically reduced conditions. Batch experiments showed that only a small proportion of Tc was rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 31 publications
(64 reference statements)
1
22
0
Order By: Relevance
“…During bioreduction, the addition of an electron donor, for example acetate, promotes microbial respiration and a cascade of terminal electron accepting process develop as the bacteria couple the oxidation of the electron donor to the reduction of available electron acceptors in the subsurface in the order oxygen > nitrate > manganese > iron > sulfate > methane. The behavior of 99 Tc during bioreduction has been well studied in sediment microcosms Eagling et al 2012;Fredrickson et al 2004;Law et al 2010), microbial cultures (Liu et al 2002;Lloyd et al 2000) and pure biomineral systems (McBeth et al 2011;Morris et al 2008;Peretyazhko et al 2012;Thorpe et al 2014).…”
Section: Mmentioning
confidence: 99%
“…During bioreduction, the addition of an electron donor, for example acetate, promotes microbial respiration and a cascade of terminal electron accepting process develop as the bacteria couple the oxidation of the electron donor to the reduction of available electron acceptors in the subsurface in the order oxygen > nitrate > manganese > iron > sulfate > methane. The behavior of 99 Tc during bioreduction has been well studied in sediment microcosms Eagling et al 2012;Fredrickson et al 2004;Law et al 2010), microbial cultures (Liu et al 2002;Lloyd et al 2000) and pure biomineral systems (McBeth et al 2011;Morris et al 2008;Peretyazhko et al 2012;Thorpe et al 2014).…”
Section: Mmentioning
confidence: 99%
“…A similar effect resulting from the low solubility of Fe re-oxidation products has been observed during Tc remobilisation from Fe rich sediments, with flow conditions promoting more Tc mobilisation compared with batch systems (Eagling et al 2012). However, iron sulphide precipitates formed under more extensively reducing conditions have been reported to act as a buffer, preventing U oxidation and/or release under flow conditions (Abdelouas et al, 1999;Moon et al, 2009).…”
Section: -mentioning
confidence: 70%
“…Uranium oxidation and/or release from geochemically reducing sediments into seawater has not, however, been investigated. (Eagling et al, 2012). A synthetic groundwater solution (pH = 7.2) representative of the Sellafield region (Wilkins et al, 2007) was prepared by dissolving salts in Milli-Q water (the constituents are shown in SI Table 1).…”
Section: -mentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have proved that tidal fluctuation has significant impact on both surface water and ground water qualities in coastal areas (Abdullah et al 1997;Kumar et al 2012). Recently, many studies have also focused on estuarine environment to understand the problem of nutrient mobilization related to salt water intrusion (Eagling et al 2012;Wong et al 2013). Salt water intrusion at estuarine region is being affected by various meteorological parameters, viz.…”
Section: Introductionmentioning
confidence: 99%